Students' perception of interactive progressive drawing using a graphic tablet in histology education: A mixed-method evaluation study - Srividya Sreenivasan (Wolters Kluwer Medknow Publications, 2023)
Background: It is important that relevant diagrams that are clear and visible are drawn by the teacher of histology for a better understanding of the subject. It is also desirable that the student see the buildup of the diagram. To achieve the same in an electronic format, a graphic tablet was used for interactive progressive drawing (IPD) in histology education. Aim and Objective: To assess students' perception of usefulness and effectiveness of IPD, in histology education. Methodology: Students were taught histology by IPD, using a graphic tablet in a classroom setting. Their perception about the method of teaching and the quality of the diagrams was obtained by an online questionnaire having open-ended and closed-ended questions. The mean and standard deviation of ratings on the Likert scale about student perception were calculated. The percentage of students who gave a rating of 4 out of 5 or above for the questions was measured as an indicator of satisfaction of the students. The answers to the open-ended questions were categorized and analyzed by the grounded theory approach. Results: A total of 137 (54.8%) students responded to the questionnaire. Seventy-eight percent of students preferred the diagrams drawn such over textbook illustrations and perceived the innovation to be helpful in improving basic understanding on a scale of 4/5 or above. Conclusion: Teaching histology by IPD using a graphic tablet was perceived by students to be better than teaching using a Power Point presentation.